Impact of Covid-19 on the Academic Achievement of Students of District Faisalabad - Umm E Habiba, Madiha Naz, Muhammad Hammad Raza, Farwa Batool, Syed Muhammad Ahmad Gillani, Sumera Shaheen, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The education of college level badly affected by the Covid-19 because of several reasons. The educational activities of college level are neglected and the education system is becoming unsatisfactory during the deteriorated era of Covid-19. Objectives: The aim of study is to identify the impact of Covid-19 on the academic achievement of student of district Faisalabad. Methodology: Total population will be 267 students of graduation 4th year in the colleges of (Government College for women Karkhana bazar Faisalabad 101, Government Degree College Samanabad 77 and Government postgraduate Islamiya College for women Eidgah road Faisalabad 89). The sample size of this study was 134 (Government college for women karkhana bazar Faisalabad 54, Government degree college Samanabad 38 and Government postgraduate Islamiya college for women Eidgah road Faisalabad 42) by the confidence interval 6% and confidence level 95%.The sample size had been determined by using online available software i.e; www.surveysystem.com. Respondents were selected for research by simple random sampling technique. The data were collected through questionnaire keeping in view the objectives of the study. Collected data were analyzed by using Statistical Package for Social Sciences (SPSS). The respondents of the present study were asked to give their opinion on a five Likert scale. The percentage, mean, standard deviation and rank order were calculated for presents the results. Conclusion: The study was concluded that students were faced numerous social problems due to the spreading of Covid-19 in all over the world. These social problems directly affected the educational system of every country. On the basis of results, it was concluded that the Covid-19 completely deteriorated the educational system and academic achievements of students. So it becomes crucial to reconstruct every fiber of educational society so that development of student’s academic achievement can be enhanced.